Effect of Acoustic Phonons on Thermoelectric Properties of Lead Iodide Nanofilms - Крамар, Валерій Максимович (Journal of Thermoelectricity, 2025)
The effect of spatial confinement on the propagation velocity of acoustic phonons in planar quasi-2D nanostructures (nanofilms) based on the layered semiconductor 2H-PbI2, thermal conductivity coefficient and thermoelectric figure of merit is investigated within the approximation of elastic continuum using the elasticity theory. It is shown that the biggest influence on the thermal conductivity of lead iodide nanofilms is exerted by acoustic phonons, which belong to the dilatational vibrations of the crystal lattice atoms. The predominant mechanism of relaxation of all types of confined acoustic phonons in a nanofilm at a moderate concentration of impurities is the phonon-phonon (Umnklapp) interaction. Its efficiency depends on the nanofilm hickness and temperature. The velocities of phonons propagation also depend on these parameters. These features lead to a rapid decrease of thermal conductivity at smaller nanofilm thickness and bigger temperature, contributing to increasing thermodynamic figure of merit of nanostructure. Estimation of the thermodynamic figure of merit for ultrathin (several layers of 2H-PbI2) films bring to the conclusion that they are suitable for the fabrication of thermoelectric devices, which can operate at room and higher temperatures.
Keywords: nanostructure, phonon, spectrum of frequencies and group velocities, thermal conductivity, thermoelectric figure of merit, thermoelectric materials, lead iodide